2010
DOI: 10.1603/me09246
|View full text |Cite
|
Sign up to set email alerts
|

A High Throughput Screening System for Determining the Three Actions of Insecticides Against <I>Aedes aegypti</I> (Diptera: Culicidae) Populations in Thailand

Abstract: Chemicals can protect humans from the bites of hemophagous arthropods through three different primary actions: irritancy (excitation), repellency, or toxicity, actions that can be evaluated using a laboratory-based assay system. In this study, the deterrent and toxic actions of three synthetic pyrethroids and DDT were characterized on six field strains of Aedes aegypti from Thailand under laboratory-controlled conditions using the high throughput screening system. All six strains showed significant contact irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Recently, HITSS has been used to define the behavioral responses among six field populations of Ae. aegypti from Thailand against three synthetic pyrethroids (Thanispong et al, 2010). From this study, it was clearly shown that the HITSS assay is an effective and easy to use tool for distinguishing the three actions of chemicals and screening new compounds.…”
Section: High Throughput Screening System (Hitss)mentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, HITSS has been used to define the behavioral responses among six field populations of Ae. aegypti from Thailand against three synthetic pyrethroids (Thanispong et al, 2010). From this study, it was clearly shown that the HITSS assay is an effective and easy to use tool for distinguishing the three actions of chemicals and screening new compounds.…”
Section: High Throughput Screening System (Hitss)mentioning
confidence: 82%
“…In general, all test populations of Ae. aegypti populations exhibit moderate to strong irritancy as compared with repellency (Grieco et al, 2005;Chareonviriyaphap et al, 2006;Paeporn et al, 2007;Thanispong et al, 2009Thanispong et al, , 2010. In addition, a few populations of Culex quinqaefacsciatus have been tested against the 3 principal classes of insecticides used in vector control; pyrethroids (deltamethrin), organophosphates (fenitrothion) and carbamates (propoxur) ( Table 3).…”
Section: Behavioral Response To Synthetic Pyrethroidsmentioning
confidence: 99%
“…Given the important role of indoor residual spraying of homes as a means of reducing risk of malaria transmission, the consequence of excitation and repellent actions should be well defined for specific malaria vectors in defined locations before and after beginning any large scale control program. Following the refinement of the ERB test system and development of the HITSS assay, both that allow the discrimination of 2 primary types of behavioral actions [12], a series of important findings on excito-repellency behavior in Anopheles mosquitoes have been reported in Thailand [19,70,125,127,137,138,142]. In general, synthetic pyrethroids consistently result in significantly stronger contact irritant responses in Anopheles compared to repellency (Table  6).…”
Section: Reviewmentioning
confidence: 99%
“…aegypti populations exposed to a series of pyrethroids (deltamethrin, permethrin, alpha-cypermethrin, cyphenothrin, d-tetramethrin and tetramethrin) have been investigated in depth in Thailand (Table  7). In general, all tested populations have exhibited moderate to strong irritancy when compared to repellency [97,101,129,140,142]. Far fewer numbers of populations of Cx.…”
Section: Reviewmentioning
confidence: 99%
“…The SRA configuration consists of one clear cylinder attached to two metal cylinders containing either control or treatment netting (see Grieco et al Thanispong et al Twenty female mosquitoes were introduced into the clear cylinder and allowed to rest for 30 s after which the butterfly valves were opened for 10 min. Following the exposure period, the number of mosquitoes in each metal and clear cylinders was recorded, including knocked‐down specimens.…”
Section: Methodsmentioning
confidence: 99%